SPIRITUAL VALUES IN GUIDANCE AND COUNSELING: SYSTEMATIC LITERRATURE REVIEW - Nurul Zahrotunnisa; Muslikah; Anwar Sutoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine spiritual values in counseling practice and their implementation in the context of education and mental health through a systematic literature review (SLR) approach. The method used is SLR with the PRISMA protocol to analyze the latest journals (2019-2025) regarding the integration of spirituality in counseling. Of the 1,245 articles identified in the initial stage, 47 articles met the inclusion criteria for the final synthesis. The results of the study indicate that spiritual values have an important role in increasing the effectiveness of counseling interventions, forming deeper therapeutic relationships, and supporting clients' psychological well-being holistically. The spiritual dimension in counseling includes aspects of the meaning of life, transcendence, connection with a higher power, and development of clients' spiritual capacities. The implementation of spiritual values in counseling can be done through an approach that respects the diversity of clients' beliefs, mindfulness-based techniques, and exploration of the meaning of life. The conclusion of this study emphasizes the importance of integrating spiritual values in modern counseling practice as an essential component for comprehensive and holistic counseling.